2013
DOI: 10.1002/14651858.cd003792.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training for asthma

Abstract: There is no conclusive evidence in this review to support or refute inspiratory muscle training for asthma. The evidence was limited by the small number of trials with few participants together with the risk of bias. More well conducted randomised controlled trials are needed. Future trials should investigate the following outcomes: lung function, exacerbation rate, asthma symptoms, hospital admissions, use of medications and days off work or school. Inspiratory muscle training should also be assessed in peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 45 publications
4
73
0
4
Order By: Relevance
“…Numerous findings on various diseases have shown no change in dynamic lung volumes after inspiratory muscle training, [11][12][13][14][15] consistent with our findings. We also investigated the effects of inspiratory muscle training on D LCO and observed no improvement.…”
Section: Pulmonary Functionsupporting
confidence: 91%
See 3 more Smart Citations
“…Numerous findings on various diseases have shown no change in dynamic lung volumes after inspiratory muscle training, [11][12][13][14][15] consistent with our findings. We also investigated the effects of inspiratory muscle training on D LCO and observed no improvement.…”
Section: Pulmonary Functionsupporting
confidence: 91%
“…21 The inspiratory muscle training was applied for 30 min/d, 7 days/week, for 6 weeks, and respiratory muscle strength consistently improved with a large treatment effect. Prior studies also demonstrated that inspiratory muscle training improves inspiratory and expiratory muscle strength in various patient populations, [11][12][13]36 similar to our findings.…”
Section: Inspiratory and Expiratory Muscle Strengthsupporting
confidence: 91%
See 2 more Smart Citations
“…In 2013 a systematic review of the training of the inspiratory muscles in asthmatics was not conclusive to support or refute the inspiratory muscle training in patients with asthma due to the small number of trials and the methodological pattern variability [8].…”
Section: Resultsmentioning
confidence: 99%